A novel model of urosepsis in mice developed by ureteral ligation and injection of Escherichia coli into the renal pelvis - Haopu Hu; Qiuxia Yan; Xinwei Tang; Shicong Lai; Ziyu Qin; Tao Xu; Hong Zhang; Hao Hu (Heliyon, 2024)
Despite extensive investigations, urosepsis remains a life-threatening and high-mortality illness. The absence of widely acknowledged animal models for urosepsis prompted this investigation with the objective of formulating a replicable murine model. Eighty-four adult male C57BL/6J mice were arbitrarily distributed into three cohorts based on the concentration of the Escherichia coli (E. coli) solution administered into the renal pelvis: Sham, Low-grade sepsis (1.0 × 108 cfu/mL), and High-grade sepsis (1.0 × 109 cfu/mL). By fabricating a glass needle with a 100 μm outer diameter, bacterial leakage during renal pelvic injection was minimized. After the ureteral ligation, the mice were injected with this needle into the right renal pelvis (normal saline or E. coli solution, 1 ml/kg). Ten days post after E. coli injection, the mortality rates for the Low-grade sepsis and High-grade sepsis groups stood at 30 % and 100 %, respectively. Post-successful modeling, mice in the urosepsis cohort exhibited a noteworthy reduction in activity, body temperature, and white blood cell count within a 2-h timeframe. At the 24-h mark post-modeling, mice afflicted with urosepsis displayed compromised coagulation functionality. Concurrently, multiple organ dysfunction was confirmed as evidenced by markedly elevated levels of inflammatory factors (IL-6 and TNF-α) in four distinct organs (heart, lung, liver, and kidney). This study confirmed the feasibility of establishing a standardized mouse model of urosepsis by ureteral ligation and E. coli injection into the renal pelvis. A primary drawback of this model resides in the mice's diminished blood volume, rendering continuous blood extraction at multiple intervals challenging.